Hubungan status gizi terhadap kejadian pre menstrual syndrome pada remaja putri di SMA Negeri 4 Palu - Idris; Enggar (MEDIA ILMU KESEHATAN, 2021)
Background: Several changes can easily take place in puberty, such as physical, cognitive, and psychosocial growth or actions. The period stage occurs in adolescence, with peak growth. Peak growth can impact changes in body structure, rapid weight, and bone life growth and physical activity, thereby influencing adolescent nutritional needs. Objective: The purpose of this study is to find out and analyze the Relationship of Nutritional Status with the incidence of Premenstrual Syndrome In Young Women in SMA country 4 Palu Methods: The study used a cross-sectional study approach, a sample used by 97 respondents. Sampling techniques with purposive sampling. Nutritional status is measured using BMI (Body Time Index) by measuring the respondent's Height and Weight. The premenstrual syndrome was measured using questionnaires by looking at emotional and behavioral physical symptoms felt at 7-10 days before menstruation. Analyze data using a chi-square test Results: of the 97 young women showed that the results of the chi-square statistical test with an α= 0.05 were obtained p-value of 0.00 <0.05. Based on the results in this study, the nutritional status in young women affects premenstrual syndrome caused by excess carbohydrates in the body where young women with 29.9% obese nutrition staus and 10.3% obesity nutritional status cause young women to experience PMS. Conclusion: There is a link between nutritional status to a premenstrual syndrome in young women in SMA country 4 Palu.